Antitumor Anesthetic Strategy in the Perioperatory Period of the Oncological Patient: A Review - Santander Ballestín, Sonia; Lanuza Bardaji, Andrea; Marco Continente, Cristina; Luesma Bartolomé, María José (Frontiers in Medicine, 2022)
The stress response triggered by the surgical aggression and the transient immunosuppression produced by anesthetic agents, stimulate the inadvertent dispersion of neoplastic cells and, paradoxically, the tumor progression during the perioperative period. We address about anesthetic agents and techniques, its relation with the metastatic development, as well as its impact on long-term survival. The scientific evidence indicates that inhaled anesthetics and opioids benefit the immunosuppression, cell proliferation and angiogenesis, providing the ideal microenvironment for the tumor progression. The likely benefit of reducing their use, or even replacing them as far as possible with anesthetic techniques which protect patients from the metastatic process, is still being investigated. The possibility of using "immunoprotective" or "antitumor" anesthetic techniques would represent a turning point in clinical practice. Through the understanding of the pharmacological mechanisms of anesthetics and their effects on tumor cells, new perioperative approaches emerge with the aim of halting and controlling metastatic development. Epidural anesthesia and propofol have been shown to maintain immune activity and reduce catecholaminergic and inflammatory responses; considering protective techniques against tumor spread. Current data generate hypotheses about the influence of anesthesia on metastatic development, although prospective trials that determinate causality are necessary to make changes in clinical practice.